Use of Grounded Theory in Information Systems Area: An Exploratory Analysis - Esteves, José (2002)
Lately, Grounded Theory method is gaining importance as a method for theory building. However, its application is not free of criticism due to lack of rigour and formality in research procedures and description of results. We analysed four cases were Grounded Theory method was used and, for each case, we identified several issues to the use of this research method. A number of recommendations and a list of critical success factors for practitioners has been generated as a result of the findings of this study. We think that this information might be useful for people that is starting a research project and want to use Grounded Theory method.